Environmentally Friendly Synthesis of Au-Te-Clustered Nanoworms via Galvanic Replacement for Wavelength-Selective Combination Cancer Therapy - Kang, Seounghun; Gil, Yeong-Gyu; Kim, Young-Jin; Kim, Young-Kwan; Min, Dal-Hee; Jang, Hongje (American Chemical Society, 2020)
Au-Te-clustered nanoworms (AuTeNWs) were successfully synthesized under ambient conditions by spontaneous galvanic replacement using Te nanorods as a sacrificial nanotemplate. Along with the gradual replacement and on-surface crystalline Au cluster formation, Te nanotemplates were transformed into a serpentine nanoworm-like morphology. The present strategy was an environmentally friendly method that did not use surfactants to control the surface structure. The synthesized nanoworms exhibited excellent photothermal conversion, photocatalytic efficiencies, and high payloads for thiolated genes and cell-penetrating peptides. According to the visible and near-infrared wavelengths of light, the photodynamic and photothermal therapeutic pathways were dominantly acting, respectively. From this, wavelength-selective combination treatment with gene therapy was successfully accomplished. Taken together, excellent therapeutic effects for in vitro and in vivo mouse models against hepatitis C replicon human hepatocarcinoma were clearly identified by using the present AuTeNWs as a phototherapeutic nanocarrier.